2015
DOI: 10.1086/681820
|View full text |Cite
|
Sign up to set email alerts
|

Fish community responses and the temporal dynamics of recovery following river habitat restorations in Europe

Abstract: Considerable uncertainty exists regarding the ability of reach-scale habitat restorations to promote ecological integrity and affect community composition in degraded streams and rivers and the time scales at which these effects take place. Restoration of habitats on the reach scale (hundreds of meters to a few kilometers) is expected to support threatened species because many of them are habitat specialists. In contrast, generalist species are predicted to be replaced in restored reaches. We used a large data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 68 publications
2
37
1
1
Order By: Relevance
“…Recent empirical models predicted the richness and total abundance of alien species invasions after restoring connectivity in a large river floodplain (Paillex et al, 2015), and the increase in alien species was pronounced within the first few years after restoration. Evidence of recolonisation by alien species was also reported after the restoration of the Rhine River (Simons et al, 2001), whereas for fishes Thomas et al (2015) found no indication that alien species particularly bene- Those native taxa that were predicted to occur without the presence of alien species, but were predicted to be absent in the presence of alien species, were further regarded as affected by the presence of alien species. In our study, we underlined that a high number of native taxa can be affected by the presence of alien species (i.e.…”
Section: Predicting the Effects Of Biological Invasions Post-restormentioning
confidence: 88%
“…Recent empirical models predicted the richness and total abundance of alien species invasions after restoring connectivity in a large river floodplain (Paillex et al, 2015), and the increase in alien species was pronounced within the first few years after restoration. Evidence of recolonisation by alien species was also reported after the restoration of the Rhine River (Simons et al, 2001), whereas for fishes Thomas et al (2015) found no indication that alien species particularly bene- Those native taxa that were predicted to occur without the presence of alien species, but were predicted to be absent in the presence of alien species, were further regarded as affected by the presence of alien species. In our study, we underlined that a high number of native taxa can be affected by the presence of alien species (i.e.…”
Section: Predicting the Effects Of Biological Invasions Post-restormentioning
confidence: 88%
“…However, because restoration of short reaches (<1 km) is often not sufficient to allow for dynamic rejuvenation of a variety of habitat types or to provide habitat for all life stages, Schmutz et al (2016) recommended that restoration should focus on dynamic, selfsustaining habitat improvement over several kilometers. In studies examining 24 and 62 European river restoration projects, respectively, Haase et al (2013) and Thomas et al (2015) found no correlation between a project's linear length and fish response or fish community composition. Muhar et al (2016) synthesized the results of these and other European studies and concluded that restoration response did not increase with project size.…”
Section: Various Restoration Measures In Idahomentioning
confidence: 97%
“…() and Thomas et al. () found no correlation between a project's linear length and fish response or fish community composition. Muhar et al.…”
Section: Does the Size Or Amount Of River Restoration Influence Fish mentioning
confidence: 99%
See 2 more Smart Citations